Autism, Accommodation and Treatment: A Rejoinder to Chong‐Ming Lim's Critique. (26th August 2015) - Jaarsma, Pier; Welin, Stellan; Dawson, Angus; Ballantyne, Angela
Abstract We are very grateful to Chong‐Ming Lim for his thoughtful reply published in this journal on one of our articles, 1 which motivated us to think more carefully about accommodating autistic individuals and treating autism. However we believe there are some confusions in Lim's argument. Lim uses the accommodation thesis, according to which we should accommodate autistic individuals rather than treat autism, as the starting point for his reasoning. He claims that if the accommodation thesis is right, then we should not treat autistic individuals for their autism, not even low‐functioning (i.e. intellectually disabled) ones, because this would be disrespectful to all autistic individuals. We should instead limit ourselves to accommodate all autistic individuals. However, the opposition between accommodation and treatment is not valid in the case of autism, because of ambiguity in the concepts of accommodation and treatment. Moreover there is confusion in Lim's reasoning caused by omitting important facts about the practice of treating autism.